ELABORATION DE L’ETUDE D’IMPACT ENVIRONNEMENTAL ET SOCIAL A L’EPREUVE DU DROIT FORESTIER CONGOLAIS - Lucien MUSAMBAY RAMAZANI (IJRDO - Journal of Social Science and Humanities Research, 2019)
The Democratic Republic of Congo abounds earthly (terrestrial) surface an important reserve of environmental ressources and from this constitute a geological scandal. It lays out a great mining, tourism potentialities etc. However, in state fragility context, the elaboration of environmental impact and social study by forester ressources mangers requires an adequate necessity nowadays in Democratic Republic of Congo. That is why the following research paper aims to : Show how elaboration of environmental impact and social study can contribute on improvement of forester management in Democratic Republic of Congo ; Subsequently to find out some consequences of mixed implementation of elaboration of environmental impact and social study in forester sector in Democratic Republic of Congo and ; Finally to suggest some susceptible remedies in order to promote the effective implementation of environmental impact and social study in Democratic Republic of Congo forester sector.